(untitled) (Sciental Journal of Education Humanities and Social Sciences, 2025)
This article is dedicated to researching the aesthetic and artistic conception of the extraordinary child character in the works of Khudoyberdi Tukhtaboyev, a prominent figure in late 20th and early 21st-century Uzbek children’s literature. In contrast to the traditional "naughty boy" typology, the extraordinary nature of the main protagonists (in works like “Riding the Yellow Giant,” “The Lad with Five Children,” “Paradise People,” “The Avenger’s Golden Head”) manifests not in psychological anomaly, but in their extremely strong inclination towards adventure, their logic that rebels against the adult world, and their satirical perception. The analysis reveals the aesthetic functions of this character, such as exposing social flaws through satire and humor, and promoting the ideas of proactiveness and resilience. The article highlights the writer’s mastery in using artistic features like hyperbole, humor, and irony in shaping the character.